2018
DOI: 10.1111/imb.12513
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptomic and genomic analysis of odorant binding proteins and chemosensory proteins in aphids

Abstract: Odorant binding proteins (OBPs) and chemosensory proteins (CSPs) play essential roles in insect chemosensory recognition. Here, we identified nine OBPs and nine CSPs from the Myzus persicae transcriptome and genome. Genomic structure analysis showed that the number and length of the introns are much higher, and this appears to be a unique feature of aphid OBP genes. Three M. persicae OBP genes (OBP3/7/8) as well as CSP1/4/6, CSP2/9 and CSP5/8 are tandem arrayed in the genome. Phylogenetic analyses of five diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 71 publications
(133 reference statements)
3
41
1
Order By: Relevance
“…Based on the number of conserved cysteines, the 10 AglyOBPs were divided into 3 subfamilies: Classic OBPs (AglyOBP2, 3, 4, 7, 8, 9, and 10), Plus-C OBPs (AglyOBP5 and 6), and Minus-C OBPs (AglyOBP11). Compared with previous aphid studies, identifying only 13, 9, 9 and 15 OBPs in Aphis gossypii, Sitobion avenae, Myzus persicae and Acyrthosiphon pisum, respectively (Zhou et al, 2010;Gu et al, 2013;Xue et al, 2016;Wang et al, 2019), we found the members of subfamilies were significantly similar between diverse aphid species. For example, although AgosOBP2-10 belong to classic OBPs, all OBP5 and OBP6 of other diverse aphid species belong to Plus-C OBPs, which indicates that Plus-C OBPs must have evolved before the divergence of the aphids from the dipterans (Zhou et al, 2010).…”
Section: Discussioncontrasting
confidence: 81%
“…Based on the number of conserved cysteines, the 10 AglyOBPs were divided into 3 subfamilies: Classic OBPs (AglyOBP2, 3, 4, 7, 8, 9, and 10), Plus-C OBPs (AglyOBP5 and 6), and Minus-C OBPs (AglyOBP11). Compared with previous aphid studies, identifying only 13, 9, 9 and 15 OBPs in Aphis gossypii, Sitobion avenae, Myzus persicae and Acyrthosiphon pisum, respectively (Zhou et al, 2010;Gu et al, 2013;Xue et al, 2016;Wang et al, 2019), we found the members of subfamilies were significantly similar between diverse aphid species. For example, although AgosOBP2-10 belong to classic OBPs, all OBP5 and OBP6 of other diverse aphid species belong to Plus-C OBPs, which indicates that Plus-C OBPs must have evolved before the divergence of the aphids from the dipterans (Zhou et al, 2010).…”
Section: Discussioncontrasting
confidence: 81%
“…4A ). This phenomenon is also observed in other insect species, such as Drosophila melanogaster Meigen (Diptera: Drosophilidae), Apis mellifera L. (Hymenoptera: Apidae), B. mori , and Myzus persicae (Sulzer) (Homoptera: Aphididae) ( Hekmat-Scafe et al 2002 , Forêt and Maleszka 2006 , Gong et al 2009 , Wang et al 2019 ). Among insect OBP s, GOBP s and PBP s are lepidopteran specific, and the location of GOBP and PBP genes on the same genomic scaffold has been found in several lepidopterans, including B. mori , M. sexta , Danaus plexippus (L.) (Lepidoptera: Nymphalidae), and S. frugiperda (Smith) (Lepidoptera: Noctuidae) ( Gong et al 2009 , Yasukochi et al 2018 ).…”
Section: Discussionmentioning
confidence: 56%
“…persicae and A . pisum species . Thus, these derivatives might have the broad‐spectrum effective responses across aphid species, suggesting a widely conserved interaction and potential for management.…”
Section: Resultsmentioning
confidence: 99%